IMPROVEMENT OF EXPANSIVE SUBGRADE USING COLUMN TECHNIQUE OF CARBIDE LIME AND RICE HUSK ASH MIXTURES - Agus Setyo Muntohar (2014)
Pavement deficiencies on expansive clay have been found as the result of the heave and shrink effect of the expansive soil during seasonal period. This paper paper presents a result of the utilization of carbide lime and rice husk ash mixture for improving performance of expansive soil. The carbide lime and rice husk ash was mixed to form SiCC columns in expansive soil. Application of the SiCC column supported flexible pavement was investigated numerically using finite element method. Two column shapes that are conventional (O-Shape) and enlarged column cap (T-Shape) were investigated in axi-symmetric model. The soil was modeled to have about 5% swelling, while 80 kN standard axle load was applied on pavement surface. The results show that the T-Shaped column can improve the settlement stability of soil between columns remarkably, while narrowing column spacing can reduce the settlement of soil effectively. A columns spacing of 3D to 5D is reasonable to reduce maximum settlement of the pavement due to heave and vehicle load.